2015
DOI: 10.1016/j.gmod.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Finite element based tracking of deforming surfaces

Abstract: We present an approach to robustly track the geometry of an object that deforms over time from a set of input point clouds captured from a single viewpoint. The deformations we consider are caused by applying forces to known locations on the object's surface. Our method combines the use of prior information on the geometry of the object modeled by a smooth template and the use of a linear finite element method to predict the deformation. This allows the accurate reconstruction of both the observed and the unob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…This work does not handle self-collisions and recent work [Smith et al 2018] has shown that ARAP and its co-rotational extension produce unacceptable artifacts when used to model human flesh, making this technique less than ideal for modeling a hand. A similar method instead performs an initial pass of surface tracking with a data term and surface regularizer followed by a solve with a volumetric tetrahedral mesh and a linear elastic model to improve tracking quality in unobserved regions [Wuhrer et al 2015]. Linear elasticity is not suited for modeling large deformations [Müller et al 2002], however, and this work is thus forced to reinitialize the mesh's rest state at each frame, leading to artificial plasticity and limiting the method to small deformations.…”
Section: Related Workmentioning
confidence: 99%
“…This work does not handle self-collisions and recent work [Smith et al 2018] has shown that ARAP and its co-rotational extension produce unacceptable artifacts when used to model human flesh, making this technique less than ideal for modeling a hand. A similar method instead performs an initial pass of surface tracking with a data term and surface regularizer followed by a solve with a volumetric tetrahedral mesh and a linear elastic model to improve tracking quality in unobserved regions [Wuhrer et al 2015]. Linear elasticity is not suited for modeling large deformations [Müller et al 2002], however, and this work is thus forced to reinitialize the mesh's rest state at each frame, leading to artificial plasticity and limiting the method to small deformations.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, we use the method of Wuhrer et al [12] to deform a template mesh M := (V, F) to match the point cloud data P. Here, V := {⃗ v i } denotes the vertex set of the mesh with ⃗ v i ∈ R 3 and F its face set. To obtain a deformation, the approach computes a set A := {A i } where A i : R 3 → R 3 is a rigid body motion for the vertex ⃗ v i by minimizing the following energy:…”
Section: Mesh Deformationmentioning
confidence: 99%
“…In order to find a minimizer A, we use a similar strategy like [12]: As a preprocessing step, we perform an automatic rigid alignment to find a good position for the template that is near the point cloud. Afterwards, we minimize a series of energies E t Def (A t ) where t ∈ [1,t max ].…”
Section: Mesh Deformationmentioning
confidence: 99%
See 2 more Smart Citations